F33: A-: B-, IncHI2/ST3, and IncI1/ST71 plasmids drive the dissemination of fosA3 and blaCTX−M−55/−14/−65 in Escherichia coli from chickens in China - Yang, Xiaoyun; Liu, Wuling; Liu, Yiyun; Wang, Jing; Lv, Luchao; Chen, Xiaojie; He, Dandan; Yang, Tong; Hou, Jianxia; Tan, Yinjuan; Xing, Li; Zeng, Zhenling; et al. (Frontiers in Microbiology, 2014)
The purpose of this study was to examine the occurrence of fosfomycin-resistant Escherichia coli from chickens and to characterize the plasmids carrying fosA3. A total of 661 E. coli isolates of chicken origin collected from 2009 to 2011 were screened for plasmid-mediated fosfomycin resistance determinants by PCR. Plasmids were characterized using PCR-based replicon typing, plasmid multilocus sequence typing, and restriction fragment length polymorphisms. Associated addiction systems and resistance genes were identified by PCR. PCR-mapping was used for analysis of the genetic context of fosA3. Fosfomycin resistance was detected in 58 isolates that also carried the fosA3 gene. Fifty-seven, 17, and 52 FosA3-producers also harbored blaCTX-M, rmtB, and floR genes, respectively. Most of the 58 fosA3-carrying isolates were clonally unrelated, and all fosA3 genes were located on plasmids belonged to F33:A-:B- (n=18), IncN-F33:A-:B- (n=7), IncHI2/ST3 (n=10), IncI1/ST71 (n=3), IncI1/ST108 (n=3), and others. The genetic structures, IS26-ISEcp1-blaCTX-M-55-orf477-blaTEM-1-IS26-fosA3-1758bp-IS26 and ISEcp1-blaCTX-M-65- IS903-iroN-IS26-fosA3-536bp-IS26 were located on highly similar F33:A-:B- plasmids. In addition, blaCTX-M-14-fosA3-IS26 was frequently present on similar IncHI2/ST3 plasmids. IncFII plasmids had a significantly higher frequency of addiction systems (mean 3.5) than other plasmids. Our results showed a surprisingly high prevalence of fosA3 gene in E. coli isolates recovered from chicken in China. The spread of fosA3 can be attributed to horizontal dissemination of several epidemic plasmids, especially F33:A-:B- plasmids. Since coselection by other antimicrobials is the major driving force for the diffusion of the fosA3 gene, a strict antibiotic use policy is urgently needed in China.